Aktivitas Komunikasi Pemasaran Joongla Melalui Word Of Mouth - Liski, Raihania Khansa; Prasetio, Arie (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
One of the areas in West Java with a huge interest in restaurants is Bandung. Joongla became the only one Pop-Up Dining Experiences in Bandung which only uses word-of-mouth for marketing communications. This research causes to be present 5T's elements word of mouth concept (Sernovitz, 2012) with qualitative case study research methods. The research shows that talkers is consumers who care about Indonesian culture and gastronomy and also enjoy spreading information about Joongla. Topics delivered by storytelling or social media. Using social media as a tool by taking a part plays an active role in providing consumer response. Tracking by seeing the performed of the customer's insight, return customer, and hashtag. There is the newest that is Typical that made the novelty through the concept of Indonesian gastronomy by utilizing media of storytelling and multisensory. Word of mouth activity that Joongla is related to the concepts of eWOM Credibility, eWOM Quality, and eWOM Quantity and also ELM theory through out Peripheral Route and Combination Route.